Flexible ultracapacitor device fabricated with an organic electrode material- naphthalene diimide nitrile/reduced graphene oxide - Deshmukh, Ashvini B.; Biradar, Madan R.; Pawar, Meenakshi D.; Bhosale, Sidhanath V.; Shelke, Manjusha V. (Journal of Energy Storage, 2022)
In this work, we have demonstrated a high-performance flexible supercapacitor electrode based on reduced graphene oxide (rGO) and naphthalene diimide nitrile (NDI-CN) composite. The rGO/NDI-CN composite was prepared by a simple approach. This composite was well characterized using various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) etc. Besides, the pi -pi stacking of NDI-CN on rGO surface was confirmed using UV-vis and FTIR techniques. As fabricated rGO/NDI-CN composite was examined as an electrode material for the supercapacitor applications. The rGO/NDI-CN electrode has delivered an excellent specific capacitance (C-sp) of 336 F g(-1) at 0.5 A g(-1)current density. The fabricated supercapacitor (SC) displays robustness with 80 % capacitance retention over 10,000 cycles at higher current density of 10 A g(-1). To further explore the real-world application of electrode materials, the corresponding flexible supercapacitor was designed and examined. The flexible device exhibited an energy density of 9.54 mu Wh cm(-2) at a power density of 0.3 mWcm(-2). These results confirmed that the rGO/NDI-CN electrode material has good potential as an energy storage device. Furthermore, the facile construction and fabrication of flexible device displayed operation of LED when fully charged. The assembled flexible supercapacitor device could be bent and twisted, signifying the potential to be used in practical applications in various high-performance electrochemical devices.
Keywords: flexible supercapacitor; Naphthalene diimide; Organic molecule electrodes; pi -pi interaction; rGO

MXenes: advances in the synthesis and application in supercapacitors and batteries - Wasnik, Kundan; Pawar, Meenakshi D.; Raphael, Leya Rose; Pullanchiyodan, Abhilash; Shelke, V. Manjusha; Raghavan, Prasanth (Journal of Materials Research, 2022)
MXenes, the newest family member of the two-dimensional materials have been widely investigated for different applications, particularly in the energy storage realm. With regard to this, MXene precursors have attained widespread attention for the application in electrochemical energy storage devices especially supercapacitors and batteries. This review has comprehensively studied various synthesis strategies adopted for MXenes including the top-down and bottom-up approaches. The shift to renewable energy alternatives have focused on the electrochemical choices such as supercapacitors and batteries, the most common and relevant ones. Thus the application of MXenes and its composite in supercapacitors as electrodes have been analyzed along with its detailed mechanism and electrochemical performance. Several battery chemistries including lithium-ion, sodium-ion and other battery systems utilizing MXenes have also been discussed here. Thus the existing strategies, advancements, and drawbacks regarding the inclusivity of MXenes in the electrochemical energy systems of supercapacitors and batteries are reviewed in this article.

Ti3C2Tx-Nb2Mo3O14 composite as novel anode to realize high power density combined with high stability in a hybrid lithium-ion capacitor - Pawar, Meenakshi D.; Thripuranthaka, Marulasiddappa; Patrike, Apurva; Deshmukh, Ashvini B.; Chaturvedi, Vikash; Krishnan, Arun; Shivade, Rajkiran; Shelke, Manjusha V. (Energy Technology, 2023)
Lithium-ion capacitors (LICs), with their higher energy density at high power capability, stand out as the future generation of energy-storage devices. Herein, the nanocomposite of Ti3C2Tx MXene with Nb2Mo3O14 is prepared by a one-step hydrothermal method and studied as an electrode material for LIC. The asfabricated composite MXene niobium molybdenum oxide (MXNMO) achieves a high reversible capacity of 205 mAh g(-1) at 100 mA g(-1) current density with outstanding cyclability. Further, asymmetric LIC full-cell device composed of MXNMO anode with supercapacitor grade activated carbon as a cathode delivers an energy density of 37.8 Wh kg(-1) (0.25 A g(-1)) and a higher power density of 4244 W kg(-1) (5 A g(-1)) along with the excellent durability showing 85% capacitance retention over 4000 cycles at 0.5 A g(-1).
Keywords: lithium-ion capacitors; MXene; niobium molybdenum oxides; pseudocapacitive anode materials

Facile synthesis of fluoride-free mxene nanosheets as an efficient anode for lithium-ion capacitor - Pawar, Meenakshi D.; Shinde, Dhanraj; Shelke, Manjusha (Chemistry-an Asian Journal, 2026)
MXenes are a promising class of two-dimensional (2D) nanomaterials known for their exceptional metallic conductivity and adjustable surface chemistry. However, the current state-of-the-art synthesis methods rely on the chemical etching of MAX phase (e.g., Ti3AlC2) with HF or fluoride-based compounds, leading to fluorine-terminated MXenes. These MXenes suffer from poor stability in ambient conditions, restricting their applications, particularly in lithium-ion-based batteries and capacitors (LIBs and LICs). In this study, we present a two-step method to produce fluorine-free MXene, addressing the stability issues of MXene in aqueous dispersions and relatively improved performance in LICs. Specifically, an efficient etching process employing hydroiodic acid (HI) with vinegar is used for the selective removal of the A layer from the MAX phase, resulting in F-free exfoliated MXenes (HVM). The HVM shows an outstanding electrical conductivity of 388 S cm(-1), maintaining high stability in aqueous dispersions over two weeks. HVM as electrode shows significantly enhanced Li+ ion storage capabilities, delivering a discharge capacity of 295 mAh g(-1) over 500 cycles at 1 A g(-1), substantially outperforming MXenes derived from F-based etching approaches. Furthermore, the HI-vinegar etching mechanism introduces unique surface functionalities that provide HVM superior cycling stability and rate capability, enabling more stable, high-performance MXene-based energy storage devices.
Keywords: 2D materials; Electrical conductivity; fluoride-free MXene; HVM anode; Lithium-ion capacitor; lithium-ion diffusion

Molecularly engineered PW12@Polypyrrole/MXene composite for high-energy, high-rate lithium-ion capacitor - Pawar, Meenakshi D.; Pandey, Priyanshi; Shelke, Manjusha (Journal of Energy Storage, 2026)
Due to inherent differences in the charge storage mechanisms of anode and cathode in a hybrid lithium-ion capacitor (LIC), a significant kinetic balance exists, necessitating the need to improve the ion/electron transfer capability of anode materials. In this study, we have developed a ternary pseudocapacitive composite comprising redox-active phosphotungstic acid nanoclusters (PW12) anchored to polypyrrole nanofibers (PPy), which are further decorated with Ti3C2Tx MXene (PW12@PPy/Ti3C2Tx) synthesized via an in-situ polymerization strategy. Here, Ti3C2Tx MXene serves as a conductive scaffold for PW12 wrapped PPy nanofibers, promoting efficient electron/ion transport. Simultaneously, the incorporation of PW12-anchored PPy nanofibers effectively mitigates the natural tendency of MXene to restack, thus preserving its layered structure. The PW12@PPy/Ti3C2Tx hybrid composite material delivers a high specific capacity of 767 mAh g-1 at 0.1 A g-1 after 100 cycles and a promising cycling stability of 280 mAh g-1 at 1 A g-1 up to 600 cycles. Moreover, an assembled LIC device using PW12@PPy/Ti3C2Tx as anode with nitrogen-doped sucrose carbon (NSC) as cathode demonstrates the highest energy density of 125 Wh kg-1 and maximum power density of 17,058 W kg-1. The device also maintains good cycling stability of 78.4 % capacity retention after 10,000 cycles at 1 A g-1. These results highlight a promising pathway for designing MXene-based hybrid composites with enhanced lithium storage performance, effectively addressing the kinetic mismatch challenges in LIC anode applications.
Keywords: Full cell device; Li ion diffusion; Lithium-ion capacitor; MXene; polyoxometalates; polypyrrole